2016
DOI: 10.1080/00016489.2016.1262553
|View full text |Cite
|
Sign up to set email alerts
|

Kabat rehabilitation for Bell’s palsy in the elderly

Abstract: The results show that, when treated only by medical therapy, the HB V subjects showed no significant age difference in relation to the achievement of a HB Grade III (100% in the over 65, 80% in the under 65), whilst, in the HB IV subjects, the younger population showed a better recovery, with 89% of a good recovery (HB I or II). In the patients who received the combined protocol, a better recovery rate was found, both in HB IV and V subjects, and the younger population could reach a good recovery in 90% of HB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 7 publications
4
48
0
1
Order By: Relevance
“…Simonetta et al demonstrated speedy recovery showing two-HB grade improvement with KR compared to the control group 1 . Our participant demonstrated four-HB grade improvement, which is in line, but much more improvement than that shown in the study by Simonetta et al 1 . Simonetta et al in another study 2 and Barbara et al 4 demonstrated speedy recovery with KR in large number of participants of different age and varied severity grades which is consistent with our fi ndings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Simonetta et al demonstrated speedy recovery showing two-HB grade improvement with KR compared to the control group 1 . Our participant demonstrated four-HB grade improvement, which is in line, but much more improvement than that shown in the study by Simonetta et al 1 . Simonetta et al in another study 2 and Barbara et al 4 demonstrated speedy recovery with KR in large number of participants of different age and varied severity grades which is consistent with our fi ndings.…”
Section: Discussionsupporting
confidence: 91%
“…Circuit training. Exercise: rest = 1:1, one session per day for 30 minutes, six days per week for 21 days 1,2,4 . KR was followed by FEFE.…”
Section: Physiotherapist Administered Kabat Rehabilitationmentioning
confidence: 99%
“…Outro ECAC, também de Monini e colaboradores, 20 de dezembro de 2016 (Quadro IV), incluiu 104 participantes admitidos no serviço de urgência de um hospital terciário, com o diagnóstico de PB severa (HB graus IV e V). Os participantes foram divididos em dois grupos com base na atitude terapêutica: grupo controlo (n=66) tratado com corticoterapia e grupo experimental (n=38) tratado com corticoterapia e MFR -método de Kabat.…”
Section: Ecacunclassified
“…This nerve damage produces an extreme asymmetrical appearance which can be especially significant in the eyes, brow and mouth regions of the face both when at rest and during the forming of facial expressions. Previous medical research [3]- [5] has highlighted the correlation between patient outcomes and the diagnosis and rehabilitation prescribed by trained medical professionals, specialised therapy plans tailored via regular feedback resulted in the best patient outcomes [6]. The potential to use such a system on a smart device has the potential to provide the clinician with more regular objective feedback on the condition and tailor therapy without always needing to physically see the patient.…”
Section: Introductionmentioning
confidence: 99%